The Historical and Cultural Traditions that Influenced the Establishment and Evolution of the Anthroponymic System in the Contemporary Karakalpak Language - Nurjamal, Awezmuratova (Indonesian Journal Publisher, 2025)
This study explores the anthropogenic system of the contemporary Karakalpak language, focusing on personal names and surnames. Through a comprehensive analysis spanning from historical-linguistic to statistical and sociolinguistic assessments, it examines the evolution and structural dynamics of Karakalpak anthroponymy. Drawing on a wide range of sources including historical archives and ethnographic data, the research categorizes and interprets the lexico-semantic and word-formation characteristics of Karakalpak names within the broader context of Turkic anthroponymy. The findings highlight the cultural and linguistic influences shaping Karakalpak naming practices amidst socio-political changes in Karakalpakstan.